2021
DOI: 10.1021/acschembio.1c00391
|View full text |Cite
|
Sign up to set email alerts
|

New Orange Ligand-Dependent Fluorescent Reporter for Anaerobic Imaging

Abstract: Bilin-binding fluorescent proteins like UnaG–bilirubin are noncovalent ligand-dependent reporters for oxygen-free microscopy but are restricted to blue and far-red fluorescence. Here we describe a high-throughput screening approach to provide a new UnaG–ligand pair that can be excited in the 532 nm green excitation microscopy channel. We identified a novel orange UnaG–ligand pair that maximally emits at 581 nm. Whereas the benzothiazole-based ligand itself is nominally fluorescent, the compound binds UnaG with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Successful application of DE-FACS to obtain P. faecium is therefore currently limited by the lack of highly-fluorescent dyes that work under fully anaerobic conditions. Recently, there has been promising work in creating anaerobic fluorescent reporter proteins [ 68 , 69 ], but microbial physiologists would greatly benefit from the creation of anaerobic fluorescent dyes for non-genetically-tractable systems. In addition to lack of strong fluorescent dye choices, some strict anaerobes, including possibly P. faecium , would likely not survive transient oxygen exposure during sorting on a commercial FACS instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Successful application of DE-FACS to obtain P. faecium is therefore currently limited by the lack of highly-fluorescent dyes that work under fully anaerobic conditions. Recently, there has been promising work in creating anaerobic fluorescent reporter proteins [ 68 , 69 ], but microbial physiologists would greatly benefit from the creation of anaerobic fluorescent dyes for non-genetically-tractable systems. In addition to lack of strong fluorescent dye choices, some strict anaerobes, including possibly P. faecium , would likely not survive transient oxygen exposure during sorting on a commercial FACS instrument.…”
Section: Discussionmentioning
confidence: 99%
“…ljungdahlii in synthetic co-cultures using FAST and the HaloTag as reporters. , Still, the HaloTag and SNAP-tag have several disadvantages, especially the long labeling times that might be challenging when co-culture dynamics are studied . Moreover, a bilin-binding fluorescent protein was recently established as a fluorescent reporter, which is functional under anaerobic conditions and might be combined with FAST for multicolor approaches. We showed that the two reporter proteins greenFAST and redFAST are suitable for use in anaerobic synthetic co-culture experiments to detect protein-producing cells as fluorescence is fast, reversible, and causes strong fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…It is pointed out that not all fluorescent proteins are well folded in E. coli. Soluble production of the bilin-binding fluorescent protein like UnaG-bilirubin as a noncovalent ligand-dependent reporter requires fusion of the solubility enhancer GST or MBP [42,43].…”
Section: Discussionmentioning
confidence: 99%